Pilihan Auditor pada Perusahaan dengan Koneksi Politik - Mitha Dwi Restuti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
This study examines whether political connected companies with tend to choose auditors. Political connected companies will choose big 4 auditors to give signal that the company is transparent to outside parties. On the other hand, political connected companies choose non-big 4 auditors because they tend to cover fraud because of loose auditor supervision. Criteria for political connections based on Faccio (2006). Political connections are measured by the politival connected members of board of director and board of commissioners to the total board members. Hypotheses testing used logistic regression. The results showed that companies with political connections tend to choose non big 4 auditors because auditors tend to be loose in supervision so they do not detect rent-seeking and tunneling behavior by companies.